KOMUNIKASI INTERPERSONAL ANTARA ORANG TUA DAN GENERAZI Z PERSPEKTIF PENDIDIKAN KARAKTER - Khasnah Syaidah; Ratna Dewi; Mujiburrohman (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
A common problem in children's character education is how parents can communicate well, both with themselves and with their children in the digital era. Social media and technology often change the way families communicate, making it difficult for parents to engage in personal reflection and in-depth dialogue. In a digital environment that is fast and full of distractions, parents may find it difficult to implement consistent and effective communication techniques for their child's character development. This research uses a qualitative approach with a literature study method. Data was obtained from books, journals and proceedings via Google Scholar, and analyzed comprehensively to be presented in the form of scientific articles. The focus of this research is how interpersonal communication between parents and generation Z can be optimized for character education. The main finding of this research is that parents' interpersonal communication plays a very important role in optimizing the character education of Generation Z through various key strategies. First, by being a role model and providing concrete examples of values such as integrity and responsibility, parents can motivate children to imitate the positive behavior they observe. Second, open discussion and dialogue allow children to develop critical thinking skills and understand character values through a constructive exchange of ideas. Third, positive reinforcement and constructive feedback, such as praise and recognition, motivate children to continue to behave in accordance with the character values taught. Fourth, through interactions with educators and peers, children learn the importance of respecting others, working together, and contributing positively to their communities, as well as values such as empathy, justice, and social responsibility. Apart from that, it is important to apply several communication techniques, such as active listening and providing emotional support to build trust and strengthen relationships; the use of clear body language and assertive communication helps avoid miscommunication and ensures messages are conveyed well;, providing constructive feedback and asking open questions facilitates a child's understanding and growth; convey empathy and apply self-disclosure techniques, where parents share personal experiences, building openness and closeness. By integrating all of these techniques, parents can create communication that supports children's character development and well-being in a holistic and sustainable manner, ensuring they receive appropriate guidance to grow into quality individuals.